2014
DOI: 10.1002/adma.201402015
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Doping Sites in Temperature‐Controlled, p‐Doped P3HT Thin Films by Conducting Atomic Force Microscopy

Abstract: The distribution of dopant sites in doped poly(3-hexylthiophene) (P3HT) thin films is characterized using optical absorption, grazing-incidence X-ray diffraction, and conducting atomic force microscopy (c-AFM). It is shown that dopant sites can be directly observed using c-AFM and that the solution temperature dramatically impacts phase separation and conductivity in spin-cast films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
148
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(155 citation statements)
references
References 34 publications
6
148
1
Order By: Relevance
“…in agreement with what was observed by Pingel et al 24 We note here that Liang and Gregg 36 observed a higher mobile hole density (~10 -16 cm -3 ), which may be a result of a less pure and lower regioregular batch of P3HT. Nevertheless, these calculations give us a reasonable estimate of the residual charge density inside pure P3HT films.…”
Section: Measurement Of Background Charge Concentration In Nominsupporting
confidence: 82%
See 2 more Smart Citations
“…in agreement with what was observed by Pingel et al 24 We note here that Liang and Gregg 36 observed a higher mobile hole density (~10 -16 cm -3 ), which may be a result of a less pure and lower regioregular batch of P3HT. Nevertheless, these calculations give us a reasonable estimate of the residual charge density inside pure P3HT films.…”
Section: Measurement Of Background Charge Concentration In Nominsupporting
confidence: 82%
“…These changes in polaronic absorption and chromophore bleaching suggest that changing temperature can control the efficiency with which dopants generate a P3HT cation in solution, as was previously reported. 24 The absorption features in the UV-visible region are analyzed and used to identify charged species after doping. As shown in Fig.…”
Section: Doping In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…decrease in σ and UV–vis anion signal28). Hence, for weakly and strongly doped P3HT, which we had deposited at 100 °C, we find a doping efficiency of ≈40% and ≈20%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[25] Doping-induced change in morphology was also reported for solution processed polymer thin films, such as poly(3-hexylthiophene) (P3HT). Duong et al [26] directly visualized the dopant distribution in P3HT:F4-TCNQ blend films using conductive atomic force microscopy (C-AFM), and showed that both dopant distribution and film morphology depend on the strength of the doping process.…”
Section: Introductionmentioning
confidence: 99%